Renal Dioctophimosis in a Dog - Vieira Nunes, Marllos Henrique (2023)
Background: Known as the “giant kidney worm,” Dioctophyma renale is the nematode that causes dioctophymosis in domestic and wild animals and in humans. Its biological cycle is indirect and dogs are definitive hosts. In this case, the adult parasite generally located in the right kidney; however, it can also be found in the left kidney, abdominal cavity, bladder, and testes. Dioctophymosis is diagnosed by visualizing parasite eggs in the urine or by visualizing the adult form using abdominal ultrasonography. This study aimed to report the occurrence of 2 cases of D. renale infection in dogs who underwent right unilateral nephrectomy, in the State of Acre, Brazil. Cases: Case 1. An adult, mixed breed bitch was treated at a private veterinary clinic in the city, having presented with a 1-month history of apathy and hematuria. During abdominal  ultrasonography, a right kidney with increased dimensions, total loss of parenchyma, and the presence of several tubular structures with anechoic content, suggestive of D. renale infestation was observed. After diagnosis, the animal was referred for nephrectomy of the right kidney, and after sectioning the capsule and renal parenchyma, the parasites were identified. Case 2. An approximately 3-year-old male, mixed breed dog, weighing 17 kg, rescued from the street by volunteers from an animal protection NGO in the city, was treated at the Teaching Veterinary Clinic of the Federal University of Acre. The animal exhibited lethargy and brown urine and had already been treated at another private veterinary clinic in the city, where an ultrasound examination had been performed that revealed the presence of the D. renale worm in the right kidney. Urinalysis of this animal revealed cloudy urine, dark yellow to greenish in color, and structures compatible with D. renale eggs (+++). The animal was referred for right unilateral nephrectomy. A total of 3 helminths measuring 25 - 40 cm in length were found inside the right kidney. D. renale was identified by considering the morphological characteristics of the worms, such as a simple mouth without lips and the presence of the copulatory bursa in males. The eggs found in the urine were elliptical in shape and brown in color, with thick walls, rough appearance, and transparent bipolar plugs. Discussion: The 2 animals described in this study were stray dogs. The change in urine color corroborates clinical findings in dogs with dioctophymosis. Dioctophyma renale is capable of generating direct renal lesions that lead to the destruction or atrophy of parenchyma of the organs and hematuria. In some cases, only the renal capsule is preserved, as in the animal reported in case 1. In both animals, the parasite was found only in the right kidney and was not present in the abdominal cavity, left kidney, testes, or bladder. Urinalysis is an excellent diagnostic tool for dioctophymosis; however, it should not be considered as the only diagnostic method, as it is not always possible to observe parasite eggs in the urine, as they are not constantly released even when adult female worms are present in the kidneys and not at all in their absence. Nephrectomy and surgical removal of parasites are the most effective methods for treating this disease in animals because there are no effective and safe antiparasitic drugs to combat the worm. The macroscopic characteristics of parts of the parasite’s body were sufficient for its identification and diagnosis of the first 2 cases of dioctophymosis in dogs in the state of Acre, Brazil. Keywords: endoparasite, parasitology, nephrectomy, nematode, kidney. Título: Dioctofimose renal em cães Descritores: endoparasita, parasitologia, nefrectomia, nematoide, rim.